2013
DOI: 10.1016/j.ibmb.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and tissue distribution of the PISCF allatostatin receptor in the red flour beetle, Tribolium castaneum

Abstract: The insect PISCF/allatostatins (ASTs) are pleiotropic peptides that are involved in the regulation of juvenile hormone biosynthesis, are myoinhibitory on the gut and the heart, and suppress feeding in various insects, but their roles in beetles are poorly understood. To provide further insight into the significance of PISCF/ASTs in beetles, the PISCF/AST receptor from Tribolium castaneum has been characterised and its tissue distribution determined. The biological activity of the T. castaneum PISCF/AST (Trica-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
5
27
3
Order By: Relevance
“…Furthermore, a peptide with homology to PISCF/AST, first identified by Veenstra [51] and called allatostatin CC (ASTCC), has also been identified. Audsley et al [6] showed that the Tribolium castaneum ASTCC activated the PISCF/AST receptor in this insect suggesting that these two peptides may have similar functions, but its role in fruit flies has not been determined.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, a peptide with homology to PISCF/AST, first identified by Veenstra [51] and called allatostatin CC (ASTCC), has also been identified. Audsley et al [6] showed that the Tribolium castaneum ASTCC activated the PISCF/AST receptor in this insect suggesting that these two peptides may have similar functions, but its role in fruit flies has not been determined.…”
Section: Discussionmentioning
confidence: 96%
“…Myosuppressin (TDVDHVFLRFamide) was also identified by its monoisotopic mass (1247.6) and the monoisotopic mass 1430.7 is in agreement with pyrokinin (PK) 1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15] (GPSASSGLWFGPRLamide). Additional mass ions present did not correspond to the masses of any predicted peptide shown in Table 1, and remain unassigned.…”
Section: Single Tissue Analysis I Corpus Cardiacummentioning
confidence: 99%
See 1 more Smart Citation
“…In Diptera two AST-C receptors have been characterized for Drosophila using Xenopus oocytes (Kreienkamp et al, 2002) and for Aedes using HEK cells (Mayoral et al, 2010). Only one AST-C receptor was found to be present in Bombyx (Yamanaka et al, 2008) and in Tribolium (Audsley et al, 2012). Activation of the Bombyx AST-C receptor elicits an increase in intracellular cAMP levels (Yamanaka et al, 2008), while the Tribolium receptor was deorphanized in HEK cells, inducing a Ca 2+ response (Audsley et al, 2012).…”
Section: Deorphanized Neuropeptide Receptorsmentioning
confidence: 99%
“…Audsley et al [8] have recently characterized the AS type C receptor in T. castaneum to provide further insight into the pleiotropic role of the peptide. Characterization and quantification of the T. castaneum AT-like receptor showed a prominent sexual dimorphism with significantly higher transcript levels in the male fat body and reproductive system [42].…”
Section: Introductionmentioning
confidence: 99%